Plan de inversión para la asociación de madres solteras unidas venceremos en la producción y comercialización de productos de panadería y pastelería para el canton Quevedo periodo 2013" - Burgos Bravo, Rocio Katherine (2013)
The present investigation called Investment Plan for Single Mothers Association "United We Shall Overcome" in the Production and Marketing of Products Baking for The Period Quevedo Canton 2013, is based on the urgent need to support the social sector from the perspective of seek the financial support of the Association consists of women entrepreneurs who seek through their daily work to meet their needs and therefore require a micro business guidance to improve their income. Seeking to answer several questions, posed the following research question "Does the design of an Investment Plan for the production and sale of bread and bakery products to benefit women who make up the Association of Single Mothers" United Venceremos "socioeconomic status is considered a contribution to support their families?, this led us to propose the following objectives; 1 "Making the situation analysis of the association of single mothers" United will win "Quevedo Canton by a SWOT" 2 "Perform a market survey to residents Quevedo to know the supply and demand in the production and marketing of bakery. "3 "Building a feasibility study to identify the technical, economic and financial costs to meet demanding project investment. The assumptions underlying this research are: General Hypothesis "The design of an investment plan for the benefit of women in the Association will utilize the resources that the government provides social projects" Specific Hypothesis 1 "The SWOT analysis will reveal the organizational structure of the association "2" the market survey conducted to help identify Quevedo population needs and consumer behavior in the consumption of products pastillaje ". 3. "The feasibility of the project will perform self-management and identify the profitability of it." For the development of the framework were taken as reference the main variables of hypotheses such as association, organizations, market research, investment plan, strategic analysis, and so on. In terms of methodology, analytical methods were applied, inductive, deductive and type of field research and literature was, we conducted a survey, and we apply a statistical formula yielded results to survey 246 people. Among the most relevant results we can mention that 89% of respondents if they eat bread and bakery products, this result indicates that our project would be welcome because we speak from a very large market. As project requirements we needed an area for Administration, a production area, a home office and an area for Bodega and human resources would be an administrator, two operators and a dispatcher, accompanied by the equipment and materials to develop products derived from flour. The unmet demand for 158,193 people, of which 5% is equivalent to 7910 people assuming that each person consumes 15 loaves per month, to be sold 12 cakes a month, 600 a month sweets and snacks, the total investment is $ 11,894.40 and its annual net flow of $ 5,878.91, which generates an NPV of $ 10,622.93 and an IRR of 40% per year, which makes the project is deemed feasible for implementation.